Katalisator Ekonomi Pedesaan: Pengaruh Kontribusi Program BUMDes terhadap Kesejahteraan Masyarakat Lokal - Sintia Olii; Frahmawati Bumulo; Sudirman; Melizubaida Mahmud; Abdulrahim Maruwae (Journal of Indonesian Economic Research, 2026)
Village-Owned Enterprises (BUMDes) serve as a strategic institutional instrument for accelerating rural economic development and poverty alleviation in developing nations like Indonesia. This study aims to investigate the empirical impact of the BUMDes program's contribution on local community welfare, focusing on a rural setting in North Sulawesi, Indonesia. Employing a quantitative approach with a descriptive survey design, data were collected proportionally from 39 rural households. The empirical analysis was conducted using simple linear regression to examine the relationship between BUMDes program contributions and community welfare. The findings reveal that the BUMDes program's contribution is perceived to be highly effective (average score 3.65), aligning with a high level of community welfare (average score 3.58). Statistical analysis confirms a positive and significant impact, evidenced by a regression coefficient of 0.484 (t-value = 4.184 > t-table = 1.687) and a coefficient of determination (R-squared) of 32.1%. These results imply that BUMDes significantly stimulates income generation, job creation, and the expansion of local business services. The study concludes that optimizing the governance and institutional capacity of BUMDes is imperative for achieving sustainable rural welfare and empowering local economic resilience.